If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -2) + 4x = 2x + -3 Reorder the terms: 5(-2 + x) + 4x = 2x + -3 (-2 * 5 + x * 5) + 4x = 2x + -3 (-10 + 5x) + 4x = 2x + -3 Combine like terms: 5x + 4x = 9x -10 + 9x = 2x + -3 Reorder the terms: -10 + 9x = -3 + 2x Solving -10 + 9x = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -10 + 9x + -2x = -3 + 2x + -2x Combine like terms: 9x + -2x = 7x -10 + 7x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 -10 + 7x = -3 + 0 -10 + 7x = -3 Add '10' to each side of the equation. -10 + 10 + 7x = -3 + 10 Combine like terms: -10 + 10 = 0 0 + 7x = -3 + 10 7x = -3 + 10 Combine like terms: -3 + 10 = 7 7x = 7 Divide each side by '7'. x = 1 Simplifying x = 1
| Y+1=-12 | | -50-4x=x+70 | | 18x^3+45r^2-2r+5=0 | | -5x+7-2x=35 | | -9+y=-23 | | 16x+4=4x-8 | | 9x-97=85-5x | | 5(n+3)=3(1-n-1) | | 4/5s-3/4s=7/10 | | -3x-4=-9-4x | | 23.1=6.6x | | 17-2(x+3)=9 | | -6x-46=-11x+74 | | (1+2x)/7+(5-x)/3=37/21 | | .11k+1.5=2.4 | | 19.79+0.8-12.3c=-19.71-14.9c | | 5x-6(x+3)=15 | | 3x-7+2x+4-7x= | | -79+x=54+8x | | a/7+5/7+2/7 | | 8b-0.5=9b | | -190-2x=-10x+50 | | y-12=-3 | | Y+2=5y-6 | | 8-9(k-3)=14k-11 | | b/5=19 | | x^2+14x=-20 | | 5x^2=2x-7 | | 4x-5(x+3)=16 | | 4+x=-13 | | 5x+21=2x+15 | | -2.86-17.1t=5.24-15.3t |